A comparative analysis of environmental policies of South African universities - Gyan, Cecilia Adwoa (Rhodes University, Faculty of Science, Department of Environmental Science, 2006)
There has been ongoing global concern on environmental issues and which is supposed to have moved down into smaller institutions and areas through local agenda 2l. Environmental issues are associated not only with care for the environment but also sustainable development. Various universities are beginning to strive for sustainable development and care for the environment. Some universities are therefore integrating care for the environment in their curricula and in their daily operations on campus. The greening of higher educational institutions as models is important as they are the seat for research and training of undergraduates who will become future leaders and policymakers and caretakers of the environment. It is therefore important for undergraduates to be exposed to greening processes in operations, research and curricula whilst still on campus. This study examines the process of formulating a policy and applies that to forming an environmental policy. The study involved a comparative analysis of environmental policies of various tertiary educational institutions from different countries. The study focused on how many universities in South Africa have environmental policies and how the universities which have environmental policies went about their formulation process. The study further examines the duration of the formulation process and the constraints encountered by universities. The study then reviews strategies on how the environmental policy is being implemented and how effective the implementation process is practically and the constraints these institutions face. The findings of the study reveal that few universities ill South Africa have an environmental policy. The universities are making efforts in their implementation process however, not all the principles found in the policies are being implemented effectively as there are no environmental management systems in place and there are no measurable objectives and targets set for proper evaluation of the success or failure of the policy.
Keywords: Environmental education -- South Africa; Sustainable development -- Study and teaching; Education, Higher -- South Africa; Universities and colleges -- Environmental aspects; Environmental policy -- South Africa; Campus planning -- Environmental aspects -- South Africa